Poverty and the international economic legal system : duties to the world's poor / [edited by] Krista Nadakavukaren Schefer. - Nadakavukaren Schefer, Krista (Cambridge University Press, 2013)
With a focus on how trade, foreign investment, commercial arbitration and financial regulation rules affect impoverished individuals, Poverty and the International Economic Legal System examines the relationship between the legal rules of the international economic law system and states' obligations to reduce poverty. The contributors include leading practitioners, practice-oriented scholars and legal theorists, who discuss the human aspects of global economic activity without resorting to either overly dogmatic human rights approaches or technocratic economic views. The essays extend beyond development discussions by encouraging further efforts to study, improve and develop legal mechanisms for the benefit of the world's poor and challenging traditionally de-personified legal areas to engage with their real-world impacts.